Dirac cones and highly anisotropic electronic structure of super-graphyne. (March 2017) - Yang, Bo; Zhou, Hongcai; Zhang, Xiaoming; Liu, Xiaobiao; Zhao, Mingwen
Abstract: Graphynes consisting of sp - and sp 2 -hybridized carbon atoms represent two-dimensional allotropes of the carbon family with intriguing properties. Based on first-principles calculations, we propose a stable three-dimensional (3D) framework (with the space group of I 4 1 / amd ) of sp - and sp 2 -hybridized carbon atoms termed super-graphyne. The exotic property of super-graphyne lies in the semi-metallic features with a highly anisotropic band structure in the reciprocal space. Along the Г-X direction, there is a Dirac cone centered at the X point with the Fermi velocity higher than that in graphene, while the bands are nearly dispersionless along the X-P direction, featured by node line Dirac semimetals. Additionally, electron spin-polarization is predicted on the bared (001) surface of super-graphyne, which preserves the semi-metallic properties. These interesting results not only enrich the 3D allotropes of the carbon family but could also find applications in electronic devices. Graphical abstract: We proposed a new carbon allotrope—super-graphyne, which is a semimetal with highly anisotropic band structure in the reciprocal space.